EXAMINING THE MEDIATING ROLE OF TAWĀḌUʿ IN REDUCING ECOLOGICAL POVERTY THROUGH ECONOMIC BEHAVIOR - Nurlisa Safitri; Syaparuddin Razak; Sitti Nikmah Marzuki; Hukmiah Husain (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2026)
This study examines the mediating role of tawāḍuʿ in reducing ecological poverty through economic behavior. It integrates the concepts of deep ecology, environmental justice, and khilāfah to explain the relationships among environmental injustice, natural resource exploitation, economic greed, sustainable environmental policy, and ecological poverty. Using a quantitative approach with SEM-PLS, data were collected from 245 Muslim middle-class respondents in South Sulawesi, Indonesia. The findings show that environmental injustice increases resource exploitation, which intensifies economic greed and leads to less responsible economic behavior while weakening tawāḍuʿ. In contrast, sustainable environmental policy enhances tawāḍuʿ, fostering ethical awareness and promoting more responsible economic behavior. Tawāḍuʿ significantly contributes to reducing ecological poverty and serves as a key mediator linking structural and behavioral factors to socio-ecological outcomes. The results indicate that ecological issues are not merely technical or economic but are also shaped by moral-spiritual dimensions that influence economic behavior. This study contributes by proposing an integrative ecological–structural–spiritual model and empirically validating the role of tawāḍuʿ within Islamic environmental ethics. Practically, it highlights the importance of integrating moral-spiritual values into sustainable environmental governance.